(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
The Clean Energy Development Bank (CEDB) has done a pioneering work to provide the loan for hydro projects without collateral under the “project financing” concept. However, a rigorous project processing regime is required to protect from any risk along with strong and continuous monitoring by the Bank. This paper highlights the requirement of technical due diligence of candidate hydro projects looking for financing. CEDB has developed and adopted a systematic hydropower project processing process Operational Policy and Guidelines. Cost-over run or time overrun due to any reason is the two major concerns for Financier as well as Developer. Rigorous screening is needed to ensure virtual risk proof lending. Hydro Nepal: Journal of Water, Energy and Environment Vol. 1, No. 2(2008) pp. 29-30